Effect of nickel doping on structure and suppressing boron volatility of borosilicate glass sealants in solid oxide fuel cells. Issue 6 (June 2019) - Ren, Mengyuan; Yang, Peng; Xu, Jing; Zhang, Qi; Chen, Kongfa; Tang, Dian; Zhuang, Haiyan; Sa, Baisheng; Zhang, Teng
Abstract: The high volatility of boron from borosilicate glass sealants often leads to boron deposition and poisoning of La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) cathode, presenting a challenge for the development of reliable solid oxide fuel cells (SOFCs). In this paper, we report that boron volatilization from borosilicate glass at 700 °C can be significantly suppressed by appropriate NiO dopant, mainly due to the increase of Si-O-B linkages in the combining B-O − and Si-O − network. Also, the formation of boron-containing phase in NiO-doping glass-ceramics has been studied, which suppresses the reaction between glass and LSCF cathode after heat treatment at 700 °C for 1000 h. Moreover, the change of crystalline phases leads to an improvement in thermal and electrical properties. We believe that our findings will open a new way for the design and development of the reliable sealing glass for SOFCs applications.